Perioperative Modification in Cirrhotic Patient Undergoing Pancreatoduodenectomy: A Case Report - Regmee, Sujan; Limbu, Yugal; Ghimire, Roshan; Maharjan, Dhiresh K; Shrestha, Suman K; Thapa, Prabin B (Journal of Institute of Medicine Nepal, 2022)
Hepatic cirrhosis can be present in patients undergoing pancreatoduodenectomy (PD). Many peri-operative measures need to be considered on such patients. A 83 years old gentleman presented with pain abdomen, Ultrasonographic evidence of dilated extrahepatic biliary system and distended gall bladder and contrast enhanced computed tomography scan of the abdomen with features of a pancreatic head mass, further confirmed to be adenocarcinoma by endoscopic ultrasound and biopsy. These findings were present on the background of Non-Alcoholic Steato-Hepatitis (NASH) associated liver cirrhosis, with Child-Turcotte-Pugh (CTP) score of 5 (CTP A) and Model For End-Stage Liver Disease-sodium (MELDNa) score of 13. The patient underwent PD. Histopathological evaluation showed a p T3 N2 moderately differentiated adenocarcinoma of the pancreatic head with Ishak scoring of liver biopsy 6. The postoperative course of the patient was uneventful and was discharged from the hospital on the 5th post-operative day. No readmission or re-operation was required.